Faktor-Faktor Risiko Kejadian Bayi Berat Badan Lahir Rendah (BBLR) Di Wilayah Kerja Puskesmas Pelaihari Tahun 2015 - Oklivia Libri; Pramono Pramono; Nor Asyanti; STIKES Husada Borneo; RSUD Ulin Banjarmasin; Alumni STIKES Husada Borneo (HB PRESS, 2016)
The infant morbidity rate has become the first indicator to determine the status of children's health, because it is a reflection of the current state of children's health. Statistically, the morbidity and mortality in developing nenonatus is high. The root cause is associated with low birth weight. LBW rate worldwide has reached 14%. Some of the factors that influence the risk of low birth weight include nutritional status, maternal age ( 35 years), parity, spacing pregnancies and chronic diseases too tight. This study was analytical with an unparalleled design case-control study. This study population all the mothers who have children/toddlers in Puskesmas Pelaihari 2015. Samples were taken from purposive sampling with 54 LBW and 54 normal children using secondary data. In general, women with a weight gain of 39 people are at risk of low birth weight (36,1%), pregnant women are at risk of low birth weight amounted to 45 (41,7 %) and anemia pregnant numbered 36 people at risk of low birth weight (33,3%). There is a correlation between the increase of pregnant women weight with LBW (p = 0,000, Î± = 0,05 and OR = 6,250), there is correlation between the circumference of the upper arm (LLA) pregnant women with LBW (p = 0,000 Î± = 0,05 and the value of OR = 6,645) and there is correlation between the levels of hemoglobin (Hb) of pregnant women with LBW (p = 0,000, Î± = 0,05 and OR = 6,192).